ESG Governance and Transparency for Public Companies in Indonesia: Legal & Policy Implications - Try Yanuaria (Ipso Jure, 2025)
This study analyzes the application of Environmental, Social, and Governance (ESG) as a legal instrument in the governance of public companies in Indonesia, focusing on normative legitimacy, regulatory effectiveness, and policy implications. Using a normative juridical research method, this study examines the Financial Services Authority Regulation (POJK) No. 51/POJK.03/2017 as the legal basis for the implementation of sustainable finance and its relationship with the principles of good corporate governance (GCG). The results of the analysis show that ESG has evolved into a binding legal norm, confirming the obligation of public companies to carry out their social and environmental responsibilities in a transparent and accountable manner. Although the legal framework has been established, there are still challenges in the aspects of regulatory harmonization, the absence of substantive sanctions, and the weak independent oversight mechanism. ESG also expands the legal responsibilities of directors and commissioners, who are obliged to ensure the integrity of reporting and the application of the principles of prudence. This research confirms that the integration of ESG into the Indonesian corporate legal system is a strategic step towards a fair, sustainable, and legal ethics-based governance paradigm. Policy reform through the establishment of the National Sustainable Governance Framework is recommended to strengthen the legal certainty and effectiveness of the implementation of ESG as a pillar of the legal legitimacy of public corporations in Indonesia